Synthesis and in vitro evaluation of three novel radiotracers for imaging of metabotropic glutamate receptor subtype 2 in rat brain. Issue 14 (15th July 2017) - Kumata, Katsushi; Yamasaki, Tomoteru; Hatori, Akiko; Zhang, Yiding; Mori, Wakana; Fujinaga, Masayuki; Xie, Lin; Okubo, Takayuki; Nengaki, Nobuki; Zhang, Ming-Rong
Graphical abstract: Abstract: The purpose of this study was to develop three new radiotracers, 1-(cyclopropylmethyl)-4-([ 11 C/ 18 F]substituted-phenyl)piperidin-1-yl-2-oxo-1, 2-dihydropyridine-3-carbonitrile ([ 11 C]1, [ 11 C]2, and [ 18 F]4 ), and to examine their specific bindings with metabotropic glutamate receptor subtype 2 (mGluR2) in rat brain sections by using in vitro autoradiography. These compounds were found to possess potent in vitro binding affinities ( K i : 8.0–34.1 nM) for mGluR2 in rat brain homogenate. [ 11 C]1, [ 11 C]2, and [ 18 F]4 were synthesized by [ 11 C/ 18 F]alkylation of the corresponding phenol precursors with [ 11 C]methyl iodide or [ 18 F]fluoroethyl bromide with >98% radiochemical purity and 80–130 GBq/μmol specific activity at the end of synthesis. In vitro autoradiography indicated that these radiotracers showed heterogeneous specific bindings in mGluR2-rich brain regions, such as the cerebral cortex, striatum, hippocampus, and granular layer of the cerebellum.